2020
DOI: 10.1097/meg.0000000000001932
|View full text |Cite
|
Sign up to set email alerts
|

Albumin administration in patients with decompensated liver cirrhosis: a meta-analytic update

Abstract: End-stage liver disease and its related complications exert a huge disease burden and reduce the survival rates of many patients. Albumin administration for patients with decompensated liver cirrhosis has been a controversial topic of discussion. The aim of this study is to investigate whether albumin reduces the mortality and complications of liver cirrhosis compared to standard medical therapy (SMT) alone. Clinical trials in which albumin administration was compared to SMT in patients with liver cirrhosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Hepatocyte-protecting drugs such as glutathione, ganning tablets, silymarin, inosine and vitamins C, E and B groups can improve liver cell metabolism, prevent fatty degeneration and protect liver cells (22). For hypoalbuminemia and ascites, although treatments such as ALB infusion and diuretics have a certain curative effect, they cannot solve the fundamental problem of DLC, thus DLC gradually leads to liver failure (23,24). The present study revealed that the routine drug treatment for DLC, which was administered for 1 year, led to no significant changes in liver function and blood indexes.…”
Section: Discussionmentioning
confidence: 54%
“…Hepatocyte-protecting drugs such as glutathione, ganning tablets, silymarin, inosine and vitamins C, E and B groups can improve liver cell metabolism, prevent fatty degeneration and protect liver cells (22). For hypoalbuminemia and ascites, although treatments such as ALB infusion and diuretics have a certain curative effect, they cannot solve the fundamental problem of DLC, thus DLC gradually leads to liver failure (23,24). The present study revealed that the routine drug treatment for DLC, which was administered for 1 year, led to no significant changes in liver function and blood indexes.…”
Section: Discussionmentioning
confidence: 54%
“…The introduction of albumin administration in the 1960s provided new ideas for treating liver cirrhosis, but whether albumin administration affects the mortality and complication rate of patients with chronic liver cirrhosis has been controversial. Some reviews have pointed out that albumin can reduce the incidence of volume overload and inflammation, thus significantly reducing the mortality of patients with liver cirrhosis, and albumin administration can also reduce the incidence of such liver cirrhosis complications as ascites, renal failure, and hepatic encephalopathy [11]. Others have expressed the opposite view, arguing that there is no evidence that long-term administration of albumin has a significant survival benefit on mortality or other complications of liver cirrhosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory results were shown in some clinical trial studies. Two previous foreign meta-analyses also explored whether albumin infusion was conducive to reducing the mortality of liver cirrhosis and the risk of relative complications, but the results were divergent [11,12]. In addition, the duration of albumin treatment for decompensated liver cirrhosis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these treatments, such as rifaximin and probiotics, in addition to acting through the ammonia pathway, also may act on inflammation. Albumin, a protein with anti-inflammatory, antioxidant and immunomodulatory properties [ 65 ], has shown some improvement in survival and clinical symptoms of HE, but these results need to be confirmed in future studies [ 66 ].…”
Section: Hepatic Encephalopathymentioning
confidence: 99%